Bai’at dalam Al-Qur’an menurut Pandangan Ibnu Katsir - Samsul Bahri; Zainuddin Zainuddin; Muhammad Husni bin Ismail (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2019)
Bai'at is one way to show a person's form of obedience to his leader. An incomplete understanding of bai'at can cause slander among Muslims. Moving on from the problem above, the author will examine Ibn Kathir's interpretation of the verses of bai'at. This research is bibliographic and data collection is done through the mauḍū'ī method. The results of the study show that the person who betrays the bai'at to the leader on the basis of obeying Allah and the Messenger, then Allah will inflict punishment on him, on the other hand, for those who obey the bai'at in matters that are ma'ruf on the basis of obeying Allah and the Messenger, then he will get a reward from Allah swt. Imam Ibn Kathir interprets the verse of bai'at as meaning